Increasing international footprint of a natural stone business - marketing plan - Marques, Cláudia Viegas e Costa (2021)
DP Stones is a Portuguese medium-sized company that works in the Cutting, Shaping and Finishing Stone business. This company has already a significant international footprint, dealing mainly with direct exports. Facing a saturated domestic market, DP aims to extend its’ life cycle and find out new ways to gain competitive advantages. Accordingly, this project will analyse the current and future state of the CSF industry and assess possible target markets for DP to expand to. Afterwards, an entry strategy and marketing plan will be developed as well as a financial plan to evaluate the viability of the project proposed.